The Phenylpropanoid Pathway Is Controlled at Different Branches by a Set of R2R3-MYB C2 Repressors in Grapevine. Issue 4 (6th February 2015) - Cavallini, Erika; Matus, José Tomás; Finezzo, Laura; Zenoni, Sara; Loyola, Rodrigo; Guzzo, Flavia; Schlechter, Rudolf; Ageorges, Agnès; Arce-Johnson, Patricio; Tornielli, Giovanni Battista
Abstract : A set of transcriptional repressors negatively regulates the expression of genes involved in different branches of the phenylpropanoid pathway. Abstract: Because of the vast range of functions that phenylpropanoids possess, their synthesis requires precise spatiotemporal coordination throughout plant development and in response to the environment. The accumulation of these secondary metabolites is transcriptionally controlled by positive and negative regulators from the MYB and basic helix-loop-helix protein families. We characterized four grapevine ( Vitis vinifera ) R2R3-MYB proteins from the C2 repressor motif clade, all of which harbor the ethylene response factor-associated amphiphilic repression domain but differ in the presence of an additional TLLLFR repression motif found in the strong flavonoid repressor Arabidopsis ( Arabidopsis thaliana ) AtMYBL2. Constitutive expression of VvMYB4a and VvMYB4b in petunia ( Petunia hybrida ) repressed general phenylpropanoid biosynthetic genes and selectively reduced the amount of small-weight phenolic compounds. Conversely, transgenic petunia lines expressing VvMYBC2-L1 and VvMYBC2-L3 showed a severe reduction in petal anthocyanins and seed proanthocyanidins together with a higher pH of crude petal extracts. The distinct function of these regulators was further confirmed by transient expression in tobacco ( Nicotiana benthamiana ) leaves and grapevine plantlets. Finally, VvMYBC2-L3 was ectopically expressed in grapevine hairy roots, showing a reduction in proanthocyanidin content together with the down-regulation of structural and regulatory genes of the flavonoid pathway as revealed by a transcriptomic analysis. The physiological role of these repressors was inferred by combining the results of the functional analyses and their expression patterns in grapevine during development and in response to ultraviolet B radiation. Our results indicate that VvMYB4a and VvMYB4b may play a key role in negatively regulating the synthesis of small-weight phenolic compounds, whereas VvMYBC2-L1 and VvMYBC2-L3 may additionally fine tune flavonoid levels, balancing the inductive effects of transcriptional activators.